(untitled) - McGrew, J. Chapman (Long Grove, Illinois, 2014)
Now in its third edition, this highly regarded text has firmly established itself as the definitive introduction to geographical statistics. Assuming no reader background in statistics, the authors lay out the proper role of statistical analysis and methods in human and physical geography. They delve into the calculation of descriptive summaries and graphics, the use of inferential statistics as exploratory and descriptive tools, ANOVA and Kruskal-Wallis tests and different spatial statistics to explore geographic patterns, inferential spatial statistics, and spatial autocorrelation and variograms.
Keywords: Địa lý,Geography; Phương pháp thống kê,Statistical methods